The Influence of Length of Business, Business Scale and Human Resource Competency on the Quality of Financial Reporting in Creative Economy Based UMKM in Jambi City - Pratenta, Christian; Kusumastuti, Ratih (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
The purpose of this study is to examine the effects of human resource competency, business size, and duration of operation on the caliber of financial reports produced by MSMEs in Jambi City that are based on the creative economy. The primary data used in this study was gathered by means of measurement techniques and questionnaire distribution. The Likert scale method is applied. Jambi City served as the site of this investigation. The participants in this study were all small business actors who were registered with the Jambi City Department of Manpower, Cooperatives, and SMEs, particularly in the Kota Baru District of Jambi City, where 776 MSMEs were registered as small business actors. Purposive sampling was used to pick the sample, which consisted of 100 MSME actors in total. This study employed a quantitative approach using data analysis tools from Multiple Liner Regression. With the aid of SPSS version 26.0 for Windows, data analysis procedures include multiple line regression analysis, t test, coefficient of determination (R2) test, data quality testing, and classical assumption testing. The quality of financial reports is affected by the length of the business; instead, the quality of financial reports is influenced by the business's scale; and finally, the quality of financial reports is influenced by human resource competency. These findings stem from the outcomes of hypothesis testing. The length of the business, the size of the business, and the competency of the human resources all have a major impact on the quality of the creative-based MSME financial reports in Jambi City.